Chromosomal synthesis of staphylococcal exfoliative toxin. - Keyhani, M (1975)
Tox-+ staphylococcal strains, as opposed to Tox-minus strains, produce epidermal exfoliation within 18 h after direct subcutaneous or intraperitoneal injection into newborn mice. The extracellular product responsible for exfoliation is termed exfoliative toxin (ET). When culture supernatant fluid from the plasmid-cured Tox-minus substrains UT 0100 or UT 0111 or from six naturally occurring phage group 2 Tox-minus strains was concentrated 20-fold and inoculated into newborn mice, ET activity could be detected. The Tox-minus, cured derivatives produced ET at levels which were 32 minus and 64-fold lower than the amounts made by their Tox-+ parent strains. Since these Tox-minus, cured substrains contained no plasmid deoxyribonucleic acid, it was postulated that the product possessing ET activity in strains UT 0100 and UT 0111 was made by chromosomal genes. This product has been isolated and purified from strain UT 0100 and appears as two faint bands after electrophoresis on polyacrylamide gels and corresponds in position to a heavy band of ET isolated from the Tox-+ strain UT 0007.